Predicting Factors of Professional Nurses’Retention in Lampang Province - Saovapha, Benjaporn; tananuchittikul, Yupin; Sripattrangkul, Sirirat; Ongkan, Thidarat (Journal of The Royal Thai Army Nurses, 2021)
The overall situation of job retention and resignation of registered nurses in Lampang province was at a high level. The mean was 3.77. When considering the 3 questions arranged in order of priority, the study found the statements “You were confident in continuing to work in this hospital” with the average of 3.98, followed by “When having problems at work, you can get help from your supervisor” with the average of 3.88, and “You are willing to continue working even though your current job did not meet expectations.” with the average of 3.69, respectively. The results of the study concerning the factors predicting the persistence of registered nurses in Lampang province revealed that there were 7 affective variables. These include 1) working environment, 2) rewarding, performances, compensation, and fair assessment, 3) relationship with the supervisors, 4) the ability to take care of family members without affecting the performances, 5) working period, 6) colleagues, and 7) the absence of the burden of taking care of the family members. All the variables accounted for 60.2% of the change in job persistence among registered nurses in Lampang province (R2 = 0.602). Additionally, the results of the study on treatment guidelines and incentives for registered nurses to remain in the system are opportunities for advancement, work evaluation, increasing manpower, salary raise, promoting the good deeds, implementation of 2P safety policy, budget support for personnel development, teamwork building, a nanny system, assigning tasks that match the practitioners’ abilities, and listening to their opinions and allowing them to participating in decision making in operations.